Applied public relations : cases in stakeholder management - McKee, Kathy Brittain; Lamb, Larry F. (New York : Routledge, 2009)
This book is a helpful mix of processes, case studies and practical advice that will help students grow as PR generalists or PR specialists. Virtually all areas of public relations are covered well in this book.
Previous ed.: Applied public relations : cases in stakeholder management / Larry F. Lamb, Kathy Brittain McKee. 2005.
Includes bibliographical references and index.
osc 04/06/13
Loan
Keywords: Public relations -- Case studies